The concept of place of Filipinos dwelling inside selected urban gated communities - Basbas, John Gabrielle D.
The inquiry on the concept of 'place' started with Heidegger's (2007, pp.53-54) claim, "to build, is to let dwell". Dwelling is the chain that connects the material in built form and the immaterial in experience (Relph, 1976). "Dwelling" and "place" (Seamon and Mugerauer, 1985) are synonymous concepts that relate to the person-environment relationship. This study sought to determine these relationships aided with the specific objectives of identifying and describing the environmental, experiential, societal, and symbolic "qualities" (Seamon and Mugerauer, 1985) of a built phenomena such as a gated community. By definition, gated communities are "physically privatized areas" (Blakely and Snyder, 1997) that is contained. This study aimed at determining the concept of "place" of Filipinos dwelling inside selected urban gated communities. Four urban gated communities were purposively selected for this study with five participants representing each community. This obtained 20 participants who were selected using snowball-purposive method. Using the overall qualitative approach of Environmental and Place Phenomenology with mixed methods that employed various strategies such as cultural probe, photo elicitation, emotion thermometers, generative sessions, semi-structured interviews, and the researcher himself as "measurement device" were utilized to collect primary and secondary qualitative data. These data were treated using iterative processes borrowed from Spiegelberg and semiology. A semiological triangle by Charles Jencks was used to identify the denotations and connotations as well as the semiotic principles of metaphor, metonym, and opposition. These semiotic processes produced "semiotic codes" which were used to answer the objectives of the study. Environmental qualities that stood out involved the interior space of the dwelling unit. Qualities such as function, planning, size and personalization are evidences that were positive. Experience also were focused mainly on the interior space of the dwelling unit, such as experiences of safety, fulfillment of domesticity, solitude, and quality time with their families were also found positive. Societal qualities showed kinship among residents as well as interactions of children were among the outstanding social qualities. Finally, the symbolic qualities that were found common among the selected gated communities was focused on two symbolism, ownership and rearing one's own family. The results also produced varied descriptions of concepts of "place" among the four selected urban gated communities. One gated community was a "place" for the welfare of children; Another as a "place" of the Filipino value of ownership; Another as a "place" of reserved, confident, and independent domestic life with the family; and another as a "place" of active kinship defined by communal unity and cooperation. Finally, the overall concept of "place" of selected urban gated communities, generated a result that focused on the Filipinos' desire for ownership and nourishment of their families, most especially their children. This core meaning influenced the formation of "dwelling", proven to have material and immaterial qualities, as the basic building blocks that shape the concept of "place" inside urban gated communities.